2021
DOI: 10.1080/19420862.2021.2002236
|View full text |Cite
|
Sign up to set email alerts
|

Rapid discovery of diverse neutralizing SARS-CoV-2 antibodies from large-scale synthetic phage libraries

Abstract: Coronavirus disease 2019 (COVID-19) is an evolving global public health crisis in need of therapeutic options. Passive immunization of monoclonal antibodies (mAbs) represents a promising therapeutic strategy capable of conferring immediate protection from SARS-CoV-2 infection. Herein, we describe the discovery and characterization of neutralizing SARS-CoV-2 IgG and VHH antibodies from four large-scale phage libraries. Each library was constructed synthetically with shuffled complementarity-determining region l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 60 publications
(108 reference statements)
1
26
0
Order By: Relevance
“…SPR experiments performed using variant S1 monomers showed the same patterns, although apparent binding affinities were in the nanomolar range (Figure 2a). These data agree with previous biophysical and functional characterizations of TB202-03 28 (CoVIC-094 in Hastie et al 29 ) that showed reduced activity of TB202-03 against S proteins bearing the L452R mutation (namely, Delta and Epsilon).…”
Section: Rbt-0813 Binds Sars-cov-2 Delta and Omicron With Picomolar Affinitysupporting
confidence: 92%
See 3 more Smart Citations
“…SPR experiments performed using variant S1 monomers showed the same patterns, although apparent binding affinities were in the nanomolar range (Figure 2a). These data agree with previous biophysical and functional characterizations of TB202-03 28 (CoVIC-094 in Hastie et al 29 ) that showed reduced activity of TB202-03 against S proteins bearing the L452R mutation (namely, Delta and Epsilon).…”
Section: Rbt-0813 Binds Sars-cov-2 Delta and Omicron With Picomolar Affinitysupporting
confidence: 92%
“…In stark contrast to antibodies that target a highly conserved Sarbecovirus epitope (e.g., sotrovimab), TB202-03 binds toward the outer edge of the receptorbinding motif of SARS-CoV-2 (the RBD-4 community in Hastie et al 29 ), does not bind SARS-CoV S1, and competes with ACE2 for SARS-CoV-2 S binding. 28 The antiviral activity of RBT-0813 may be explained by the fact that none of the key residues in the TB202-03 epitopenamely, N450, I472, and F490 28 -are mutated in Omicron.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These camelid heavy chain variable domains, can be expressed as a single domain, typically referred to as a “nanobody,” with a molecular weight of about 12 kDa, roughly 1/12th that of the full-length IgG, and 1/80th the size of the IgM isotype described above. Other typical sources of single domain antibodies are camelid antibody libraries [ 339 ] and libraries of engineered human single domain antibodies [ 340 ].…”
Section: Anti-sars-cov-2 Igg Antibodiesmentioning
confidence: 99%